Proximal Femoral Morphology and the Relevance to Design of Anatomically Precontoured Plates: A Study of the Chinese Population - Kun-Jhih Lin; Hung-Wen Wei; Kang-Ping Lin; Cheng-Lun Tsai; Pei-Yuan Lee (The Scientific World Journal)
Adequately shaped femoral plate is critical for the fixation of fracture in the pertrochanteric regions. Lateral aspect of greater trochanter is an important region where the proximal femoral plate anchored. However, little is known regarding the morphology of greater trochanter. The objective of this study was to measure main dimensions of greater trochanter and other regions in the proximal end of the femur to provide an anatomical basis for the design of the proximal femoral plate. Anthropometric data on the proximal femur were performed utilizing three-dimensional computational modeling. Computed tomography images of healthy femurs in 53 women and 47 men were contributed to three-dimensional femur modeling. All data were compared between male and female femora. The results showed that mean values for male group were found to be greater in most of measured femoral dimensions. Oppositely, females demonstrated higher neck-shaft angle on anteroposterior view and femoral anteversion angle. The anthropometric data can be used for the anatomical shape design of femoral plates for osteosynthesis of fractures in the trochanteric regions. A distinct plate design may be necessary to accommodate differences between the genders.